'The Woman was a Stranger': childbirth and community in eighteenth-century England*. Issue 3 (16th April 2019) - Fox, Sarah
ABSTRACT: On 17 December 1766 James Field stood accused at the Old Bailey of the 'wilful murder of a new born child, by casting it into a tub of water'. The case was exceptional in many ways—not only was the accused male but he and his family had removed themselves from the network of neighbourly interactions that characterised lower status life in this period. As a result, the court's deposition statements record ideas of belonging and community with unusual clarity. Using Field as a case study, this article explores the involvement of the local community in the experience of childbirth in the eighteenth century. It will argue that childbirth had an active role in the creation of neighbourhood, and momentarily captured shifting eighteenth-century understandings of community.